Reflections on the Neoclassical Dispositions of a Banned Playwright - Ellodi, Denise (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2025)
The literary work of Albanian playwright Etëhem Haxhiademi had been banned for over four decades due to vindictive political principles. He was one of the most notable creators of Albanian tragedy, revealing Albanian literature in the modern era. In 1924, he wrote the tragedy "Ulysses" in Berlin, in 1926 he wrote the tragedy "Achilles" in Vienna, and in 1928 he wrote the tragedy "Alexander" in Lushnje, Albania. All three tragedies were published in Tirana, Albania, in 1931. Later, he wrote and published the tragedies "Pyrrhus" (1934), "Scanderbeg" "Skënderbeu" (1935), "Diomedes" (1936), and "Abeles" (1938). He was also known as the creator of the poetic volume "Lyra", (1939). His dramatic work was set up according to models of classical tragedy, using ancient or medieval subjects, even dating back to pre-biblical history. His literary work becomes functional to revelations that can be compared to phenomena, ideas and problems staging the reality of the time in which he wrote his works. By striving to clarify the notions of classicism in this writing, we have directly contributed to the estimation of the literary work of E. Haxhiademi which, in our opinion, presents excessive concomitances in the ideas, aesthetic ideals and design practices of neoclassical experiments. in Europe.